Production of Rhamnolipids from Soybean Soapstock: Characterization and Comparation with Synthetics Surfactants - Lopes, Paulo Renato Matos [UNESP]; Montagnolli, Renato Nallin; Cruz, Jaqueline Matos [UNESP]; Lovaglio, Roberta Barros; Mendes, Carolina Rosai [UNESP]; Dilarri, Guilherme [UNESP]; Contiero, Jonas [UNESP]; Bidoia, Ederio Dino [UNESP] (Springer Nature, 2020)
Abstract: In this study, waste from the soybean industry was used as the main carbon source to produce rhamnolipids. This biosurfactant have a great value and can be used in several applications. The biosurfactant produced in this study was characterized through to HPLC–UV, and the emulsification index was determined. The work also made a biodegradation test of lubricating oil residue, using the biosurfactant produced and other synthetics surfactants to make a comparison. After 120 h the total production concentration was 1.434 g L−1 of rhamnolipids. This value was close to order works that used more noble carbon source for fermentation. Also was possible to identify two different homologous on the fermentation production (Rha2C10C10 and Rha2C10). The rhamnolipids synthesized also showed good results in the emulsification of lubrication oil residue, being very close to the synthetic alternative Tween80. Thus, it is possible to conclude that the biosurfactant produced has potential for application in bioremediation of oils residues, and can be an efficient substitute for synthetic surfactants. Graphic Abstract: [Figure not available: see fulltext.].
Keywords: Bioremediation; Biosurfactant; Colorimetric; Fermentation; Oil; Pseudomonas aeruginosa